THE SPECIFY OF THE CALCULATION OF THE DENSITY OF TECHNICAL AMMONIA WHICH ARE PUMPED BY AMMONIA PIPELINE - Рис, Віталій Васильович; Сусак, Олександр Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The method of calculating of the density of technical ammonia which are pumped by ammonia pipeline was proposed. The ammonia density is determined based on the second virial coefficient, the density of water is determined according to the equation Gibbs energy taking into account absolute pressure and temperature of water